A New ZVT-ZCT-PWM DC-DC Converter - Aksoy, Ismail; Bodur, Haci; Bakan, A. Faruk (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
In this study, a new snubber cell is developed in order to increase the power density and the efficiency in pulsewidth modulation (PWM) converters and to decrease the EMI noise. The developed snubber cell provides main switch both to turn on with zero-voltage transition (ZVT) and to turn off with zero-current transition (ZCT). The converter incorporating this snubber cell operates with soft switching (SS) in a wide range of line and load voltages. Also, all semiconductor devices in the converter operate with SS. There is no additional voltage stress in the main components, and the stresses of the auxiliary components are negligible. The new converter has a simple structure, low cost, and ease of control as well. The operation principle and detailed steady-state analysis of the ZVT-ZCT-PWM boost converter with new snubber cell are presented. The presented theoretical analysis is verified exactly by a prototype of 100 kHz and 500 W converter. Also, the overall efficiency of the new converter has reached a value of 98.3% at nominal output power.
Keywords: DC-DC converter; soft switching (SS); zero-current transition (ZCT); zero-voltage transition (ZVT); FAMILY; Engineering